Purely electronic zero-phonon line as the foundation stone for high-resolution matrix spectroscopy, single-impurity-molecule spectroscopy, and persistent spectral hole burning. Recent developments - Rebane, K.K. (Физика низких температур, 2003)
A few examples of recent progress in the study and applications of purely electronic zerophonon line (ZPL) and its offshoots are briefly considered: new experimental values of the narrowest ZPL; time-and-space-domain holography in the femtosecond domain, and the realization of a femtosecond Taffoli gate by it; single-impurity-molecule spectroscopy, its relation to single-photon interference and to the realization of quantum computing; the promises of quantum computing compared to what has already been done in holography.